Phosphate enriched polyoxometalate based ionic salts for proton conduction - Dey, Chandan; Kundu, Tanay; Aiyappa, Harshitha Barike; Banerjee, Rahul (RSC Advances, 2015)
A series of [NiMo12O30(PO4)(8)](n-) POM anion and organic cation based ionic composites have been prepared in hydrothermal conditions. The ionic composites with protonated ethylene diamine molecules have been tested for proton conductivity.